Impact of concomitant aortic regurgitation on long-term outcome after surgical aortic valve replacement in patients with severe aortic stenosis - Gradinac Sinisa; Djukanovic Bosko; Milojevic Predrag; Nezic Dusko; Tasic Nebojsa; Popovic Zoran B; Catovic Suad; Angelkov Lazar; Otasevic Petar (Journal of Cardiothoracic Surgery, 2011)
Abstract Background Prognostic value of concomitant aprtic regurgitation (AR) in patients operated for severe aortic stenosis (AS) is not clarified. The aim of this study was to prospectively examine the impact of presence and severity of concomitant AR in patients operated for severe AS on long-term functional capacity, left ventricular (LV) function and mortality. Methods Study group consisted of 110 consecutive patients operated due to severe AS. The patients were divided into AS group (56 patients with AS without AR or with mild AR) and AS+AR group (54 patients with AS and moderate, severe or very severe AR). Follow-up included clinical examination, six minutes walk test (6MWT) and echocardiography 12 and 104 months after AVR. Results Patients in AS group had lower LV volume indices throughout the study than patients in AS+AR group. Patients in AS group did not have postoperative decrease in LV volume indices, whereas patients in AS+AR group experienced decrease in LV volume indices at 12 and 104 months. Unlike LV volume indices, LV mass index was significantly lower in both groups after 12 and 104 months as compared to preoperative values. Mean LVEF remained unchanged in both groups throughout the study. NYHA class was improved in both groups at 12 months, but at 104 months remained improved only in patients with AS. On the other hand, distance covered during 6MWT was longer at 104 months as compared to 12 months only in AS+AR group (p = 0,013), but patients in AS group walked longer at 12 months than patients in AS+AR group (p = 0,002). There were 30 deaths during study period, of which 13 (10 due to cardiovascular causes) in AS group and 17 (12 due to cardiovascular causes) in AS+AR group. Kaplan-Meier analysis showed that the survival probability was similar between the groups. Multivariate analysis identified diabetes mellitus (beta 1.78, p = 0.038) and LVEF < 45% (beta 1.92, p = 0.049) as the only independent predictor of long-term mortality. Conclusion Our data indicate that the preoperative presence and severity of concomitant AR has no influence on long-term postoperative outcome, LV function and functional capacity in patients undergoing AVR for severe AS.